Readout interfacing circuit for natural frequency detection of MEMS resonator: article / Hasliadi Guliga - Guliga, Hasliadi (2013)
This paper presents the readout interfacing circuit (ROIC) for natural frequency detection of MEMS resonator. It is reported that the MEMS Resonator vibrate at specific natural frequency under different condition. Therefore, the main aim of this research is to design the interfacing circuit to capture the current in order to analyze resonator frequency behavior. The work is focused on the development of ROIC prototype design with the MEMS resonator emulator included. The architecture of ROIC is mainly based on two blocks: transimpedance and instrumentation amplifier where this design is simulated using Multisim and implemented on PCB level. Simulation result of MEMS Resonator emulator model shows, it produces a current of 2.89nA at 22kHz natural frequency which is close to published works. Simulation result of ROIC with MEMS emulator model produces 10.7mVrms at 21kHz with 10 gain. The ROIC hardware implementation with practical values of RLC produces 0.624Vrms as compared in simulation process produces 1.46Vrms at the same 1.5kHz natural frequency even though the theoretically produces 1.6KHz natural frequency. As conclusion, it is shown that the ROIC is able to capture the natural frequency with 95.5% accuracy compared to the theoretical value.